2014
DOI: 10.1007/s12026-014-8577-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of systemic lupus erythematosus flares during pregnancy

Abstract: This review examines the risk factors for the development of systemic lupus erythematosus (SLE) flares during pregnancy. In preconception, anti-DNA, hypocomplementemia, previous thrombosis, triple antiphospholipid (aPL) antibody positivity, active lupus nephritis and discontinuation of medications such as hydroxychloroquine and azathioprine are factors associated with pregnancy failure. During pregnancy, SLE flares are associated with aPL antibodies, synergic changes of pregnancy on Th1 and TH2 cytokines, othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 55 publications
2
40
0
3
Order By: Relevance
“…These findings suggest that azathioprine is not only safe but also necessary to control the activity, and to reach a fetal outcome similar to patients not exposed to this drug. In fact, discontinuation of medications such as hydroxychloroquine and azathioprine is associated with poor fetal outcome [15].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that azathioprine is not only safe but also necessary to control the activity, and to reach a fetal outcome similar to patients not exposed to this drug. In fact, discontinuation of medications such as hydroxychloroquine and azathioprine is associated with poor fetal outcome [15].…”
Section: Discussionmentioning
confidence: 99%
“…[26,44] Additionally, PIH is associated with increased risk for lupus flares during pregnancy or postpartum. [24,27] However, only a few studies have examined whether experiencing PIH is associated with an increased risk for developing SLE in the future. A Danish population-based cohort study revealed that the risk for developing any autoimmune disease was significantly increased among women with gestational hypertensive disorders (IRR = 1.21; 95% CI 1.16–1.26).…”
Section: Discussionmentioning
confidence: 99%
“…[2426] Moreover, preeclampsia is associated with lupus flares. [24,27] Very few studies have examined the relationship between PIH and the risk of SLE. Therefore, we conducted a nationwide population-based retrospective cohort study to investigate the risk for developing SLE among patients who have had PIH.…”
Section: Introductionmentioning
confidence: 99%
“…This special issue examined more conventional aspects of pregnancy in the context of autoimmunity. Two authors have questioned predictive factors of SLE flares as well as of obstetric and fetal complications during pregnancy [6,7]. Despite considerable progress in the identification of pre-conception, per pregnancy and puerperium risk factors for lupus flare, summarized by Jara et al [7], it appears that predictive factors in pregnancy have not been systematically and fully elucidated.…”
mentioning
confidence: 99%
“…Two authors have questioned predictive factors of SLE flares as well as of obstetric and fetal complications during pregnancy [6,7]. Despite considerable progress in the identification of pre-conception, per pregnancy and puerperium risk factors for lupus flare, summarized by Jara et al [7], it appears that predictive factors in pregnancy have not been systematically and fully elucidated. However, by prospectively following 132 pregnancies in 96 SLE patients, Borella et al [6] reported that the number of flares before conception best predicted the risk of lupus flares during pregnancy.…”
mentioning
confidence: 99%